2018 learning report on implementation of the accountability mechanism policy. (Metro Manila, Philippines Asian Development Bank, 2019)
ADBs 2012 Accountability Mechanism Policy mandates a triennial analysis of lessons learned, with a focus on the management of complaints elevated to this last resort mechanism. This report attempts to put into perspective the number, nature, and management of complaints from project-affected people as dealt with by project level grievance redress mechanisms (GRMs) and by operational departments. It finds that most complaints are effectively addressed by GRMs and that the number of projects with complaints reaching the Accountability Mechanism is a small fraction of ADBs active portfolio. The recommendations are aimed at improving the future implementation of the policy.
Keywords: Public administration; Governance and public sector management; Electronic books